삼중수소 측정 신뢰성 검증을 위한 국제숙련도시험 결과 평가 - 장희진(Hee Jin Jang); 김효진(Hyo Jin Kim); 계용욱(Yong-Uk Kye); 이지은(Ji Eun Lee); 이창근(Chang-Geun Lee); 조월순(Wol Soon Jo); 백정화(Jeong-Hwa Baek); 이동연(Dong-Yeon Lee); 강영록(Yeong-Rok Kang) (Journal of Radiological Science and Technology, 47(6), 2024)
Participation in proficiency test (PT) is a valuable tool for external quality control that provides an opportunity to improve analytical skills and techniques in the field of radioactivity measurements. Participation in proficiency tests is an essential requirement of ISO/IEC 17025. Accordingly, in order to secure the reliability of tritium analysis results, our institution participated in the Environmental Resources Association's (ERA) tritium radioactivity international proficiency test certified by the American Calibration Testing and Accreditation Agency (A2LA). The 2024 American Institute of Environmental Resources (ERA)'s tritium proficiency test was conducted by analyzing 250 mL of unknown water samples within the range of 1,000 to 24,000 pCi/L from a liquid scintillation counting (LSC). The results were evaluated on the accuracy and precision criteria adopted by the ERA　proficiency testing　group. Z-score was used as an evaluation method, and reliability was recognized if |z|≤2 was satisfied as a z-score evaluation standard.　The z-score result of this study was 0.0331, which was satisfied, and the quality system and technical capabilities of the radioactivity measurement institute were checked through participation in the international proficiency test, resulting in contributing to the improvement of the reliability of the test results. 숙련도 시험(PT)은 방사능 측정 분야에서 분석 기술와 능력을 향상시킬 수 있는 기회를 제공하는 외부 품질 관리를 위한 유용한 방법으로, 숙련도 시험의 참여는 ISO/IEC 17025의 필수 요건이다. 이에 본 기관에서 삼중수소 분석 결과의 신뢰성을 확보하기 위하여 미국 교정시험기관 인정기구(A2LA)로부터 인증을 받은 환경 자원 협회(ERA)의 삼중수소 방사능 국제 숙련도 시험에 참여하였다. 2024년 미국 환경 자원 협회(ERA)의 삼중수소 숙련도 시험은 액체 섬광 계수(LSC)로 1,000~24,000 pCi/L 범위 내의 미지의 물 시료 250 mL를 분석하여 진행되었다. 시험 결과는 ERA 숙련도 시험 그룹에서 채택한 정확도와 정밀도 기준에 따라 평가되었다. 평가 방법으로 z-score를 사용하였으며, z-score의 평가 기준으로 |z|≤2 만족한다면 신뢰성이 확립한다고 판단된다. 본 연구에서 z-score는 0.0331로 만족하는 결과를 얻었으며, 국제 숙련도 시험 참여를 통해 방사능 측정 기관의 품질 체계와 기술 능력을 확인하여 시험 결과의 신뢰성 향상에 기여하였다.